Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Untuk Meningkatkan Hasil Belajar Siswa Pada Tema Lingkungan Sahabat Kita - Jenni Parlopes Br Tarigan; Dewi Anzelina; Anton Sitepu; Nova Florentina; Ester Julinda Simarmata (Journal on Education, 2023)
Theoretically, the quality of learning greatly affects the success of learning. So that the quality of learning has a directly proportional relationship with learning outcomes, which means that the higher the quality of learning, the higher the learning outcomes obtained. In Curriculum 2013 thematic learning is integrated learning using themes to link several subjects so that it can provide meaningful experiences for students. Based on information from the fifth grade teacher of SD Negeri 101816 Pancur Batu that student learning outcomes are still low. This is because teachers do not apply learning models in the learning process, so that students are less active in the learning process, and the teaching and learning process in the classroom also feels boring because, teachers are more active than students. And learning activities in the classroom are one-way (conventional), which results in low student learning outcomes. Based on the analysis and discussion of the results of research conducted in class V of State Elementary School 101816 Pancur Batu in the 2022/2023 learning year, it can be concluded that the implementation of learning by using the Make A Match Type Cooperative Learning Model on the theme of Our Friends Environment subtheme Environmental Changes in class V of State Elementary School 101816 Pancur Batu in the 2022/2023 learning year is categorized as good. It can be seen from the results of students learning outcome improvement in cycle I obtained as much as 68% of the sufficient category and in cycle II increased to 96% of the very good category.